STUDENT PERSPECTIVE AS AGENT OF CHANGE THROUGH EDUCATION - Rofia Abada; Soumia Bentahar; Henny Ramdaniar (JURNAL EDUSCIENCE, 2023)
This study aims to determine: Studentâ€™s perspective as an agent of change. The research method used is a qualitative method. Data collection techniques using observation and interviews. The data processing technique uses triangulation. Data analysis used inductive analysis, namely data reduction, unitization and categorization, data display and conclusion drawing. The results showed that: 1. Students as agents of change, namely students have an important role in a change regardless of the level of society or economic status, the intended changes are students who are agents of change, guardians of values, successors of the nation, moral strength and social control. 2. The role of civic education in shaping students as agents of change through several stages, namely: through cognitive, affective, and psychomotor instilled through civic education. Students as the agent of change students have significant roles in a change without seeing society or economic status, changes in intent students the agent of change, the value, a the next generation, of moral strength and social controlÂ Keyword: College Student; Agen of Change; Education